Problematyka kaliningradzka na łamach „Gazety Olsztyńskiej” w latach 2015−2019: The issue of Kaliningrad in “Gazeta Olsztyńska” in the years 2015–2019 - Żmijkowska, Magdalena (Przegląd Wschodnioeuropejski, 2019)
The article is a presentation of the results of the analysis of the (quantitative and qualitative) content of “Gazeta Olsztyńska” in the field of issues of the Kaliningrad region in 2015–2019. The Olsztyn daily is for the inhabitants of the Warmian-Masurian region one of the sources of knowledge about the Kaliningrad region and its inhabitants. The texts published in “Gazeta Olsztyńska” are also a reflection of the internal political situation and prevailing Polish-Russian relations. They are also one of the ways to promote economic cooperation and cultural exchange in the Warmian-Masurian Voivodeship and the Kaliningrad District.